Disease‐specific phenotypes in iPSC‐derived neural stem cells with POLG mutations. Issue 10 (25th August 2020) - Liang, Kristina Xiao; Kristiansen, Cecilie Katrin; Mostafavi, Sepideh; Vatne, Guro Helén; Zantingh, Gina Alien; Kianian, Atefeh; Tzoulis, Charalampos; Høyland, Lena Elise; Ziegler, Mathias; Perez, Roberto Megias; Furriol, Jessica; Zhang, Zhuoyuan; et al.
Abstract: Mutations in POLG disrupt mtDNA replication and cause devastating diseases often with neurological phenotypes. Defining disease mechanisms has been hampered by limited access to human tissues, particularly neurons. Using patient cells carrying POLG mutations, we generated iPSCs and then neural stem cells. These neural precursors manifested a phenotype that faithfully replicated the molecular and biochemical changes found in patient post‐mortem brain tissue. We confirmed the same loss of mtDNA and complex I in dopaminergic neurons generated from the same stem cells. POLG‐driven mitochondrial dysfunction led to neuronal ROS overproduction and increased cellular senescence. Loss of complex I was associated with disturbed NAD + metabolism with increased UCP2 expression and reduced phosphorylated SirT1. In cells with compound heterozygous POLG mutations, we also found activated mitophagy via the BNIP3 pathway. Our studies are the first that show it is possible to recapitulate the neuronal molecular and biochemical defects associated with POLG mutation in a human stem cell model. Further, our data provide insight into how mitochondrial dysfunction and mtDNA alterations influence cellular fate determining processes. Synopsis: Mutations in the POLG gene cause mitochondrial disease with devastating phenotypes in patients. Neural stem cells generated from patient iPSCs showed mitochondrial dysfunction and mtDNA depletion, leading to loss of complex I with concomitant ROS overproduction and disturbed NAD + metabolism. Human iPSCs carrying POLG mutations can be differentiated into high‐yield neural stem cells (NSCs). NSCs with disease caused by POLG mutations showed energy failure and mtDNA depletion, similar to findings in iPSC‐derived dopaminergic neurons. POLG NSCs recapitulated the disease phenotypes observed in POLG patient post‐mortem tissues. POLG NSCs showed loss of mitochondrial complex I and abnormal UCP2/SirT1 mediated NAD + homeostasis associated with overproduction of intercellular and mitochondrial reactive oxygen species (ROS). Elevated ROS triggered cell senescence and BNIP3‐mediated mitophagy, which contributes to pathological mechanisms in mitochondrial diseases. Abstract : Mutations in the POLG gene cause mitochondrial disease with devastating phenotypes in patients. Neural stem cells generated from patient iPSCs showed mitochondrial dysfunction and mtDNA depletion, leading to loss of complex I with concomitant ROS overproduction and disturbed NAD + metabolism.